Foundations of play therapy - Schaefer, Charles E. (Hoboken, N.J. : Wiley, 2011)
"Edited by Charles Schaefer, the "father of play therapy," this fully updated and revised Second Edition of Foundations of Play Therapy provides in-depth coverage of all the major models of play therapy from leading play therapists. Expert contributors provide detailed descriptions of all the major theoretical approaches to play therapy. Each chapter is fully revised and provides up-to-date discussions of the latest developments, applications, and empirical support for each theory. Play therapists and other mental health professionals will benefit from this landmark text"--Provided by publisher.
pt. I. Fundamentals of play therapy practice. Play therapy: basic concepts and practices / Julie Blundon Nash and Charles E. Schaefer -- The therapeutic powers of play and play therapy / Charles E. Schaefer and Athena A. Drewes -- Playing it safe: ethical issues in play therapy / Cynthia A. Reynolds and Laura J. Tejada -- pt. II. Major theoretical approaches. Psychodynamic models : Psychoanalytic approaches to play therapy / Alan J. Levy ; Jungian analytical play therapy / Eric J. Green ; Adlerian play therapy / Terry Kottman ; Release play therapy / Heidi Gerard Kaduson -- Humanistic models : Child-centered play therapy / Daniel S. Sweeney and Garry L. Landreth ; Filial therapy: strengthening family relationships with the power of play / Risë VanFleet ; Gestalt play therapy / Violet Oaklander ; Experiential play therapy / Carol C. Norton and Byron E. Norton -- Systemic models : Family play therapy: igniting creative energy, valuing metaphors, and making changes from the inside out / Eliana Gil ; Group play therapy / Daniel S. Sweeney ; Ecosystemic play therapy / Kevin O'Connor -- Emerging models : Theraplay: attachment-enhancing play therapy / Evangeline Munns ; Solution-focused play therapy: helping children and families find solutions / Donald R. Nims ; Cognitive-behavioral play therapy / Susan M. Knell ; Narrative play therapy / Aideen Taylor de Faoite ; Integrative play therapy / Athena A. Drewes ; Prescriptive play therapy / Charles E. Schaefer.
"Edited by Charles Schaefer, the "father of play therapy," this fully updated and revised Second Edition of Foundations of Play Therapy provides in-depth coverage of all the major models of play therapy from leading play therapists. Expert contributors provide detailed descriptions of all the major theoretical approaches to play therapy. Each chapter is fully revised and provides up-to-date discussions of the latest developments, applications, and empirical support for each theory. Play therapists and other mental health professionals will benefit from this landmark text"--Provided by publisher.
Includes bibliographical references and indexes.
Keywords: Play therapy; Play Therapy